Type D personality is associated with depressive symptoms and clinical activity in inflammatory bowel disease. Issue 1 (11th May 2021) - Jordi, Sebastian Bruno Ulrich; Botte, Federica; Lang, Brian Matthew; Greuter, Thomas; Krupka, Niklas; Auschra, Bianca; Schreiner, Philipp; Sulz, Michael Christian; Biedermann, Luc; von Känel, Roland; Rogler, Gerhard; Begré, Stefan; et al.
Summary: Background: Inflammatory bowel disease (IBD) can be exacerbated by stress and depression. Type D personality, characterised by high negative affectivity and social inhibition, represents a vulnerability towards stressors and is associated with adverse outcomes in coronary heart disease. Aims: To assess the prevalence of Type D personality in IBD patients and investigate potential associations with disease course. Methods: We tested for associations between Type D ( Type D Scale‐14 ), depressive symptoms ( Hospital Anxiety and Depression Scale's depression subscore ≥11) and recurrent IBD amongst Swiss IBD cohort patients. We built regression models for cross‐sectional and Cox proportional hazards models for time‐to‐event analyses. IBD disease course was assessed by the future occurrence of active disease ( Crohn's Disease Activity Index ≥150/ Modified Truelove & Witts activity index ≥10) and several IBD‐relevant endpoints. Results: Amongst 2275 patients (1005 ulcerative colitis, 1270 Crohn's disease), 672 (29.5%) had Type D. Type D was a significant risk factor for future active disease (adjusted hazard ratio, aHR: 1.60, corrected P value, q = 0.007) and predicted the future presence of depressive symptoms (aHR: 3.30, P  < 0.001). The combination of Type D and depressive symptoms further increased the risk for active disease (aHR: 3.98, q < 0.001). However, Type D associated depressive symptoms seemed to be the main contributor to this effect as Type D's predictive power decreased considerably in models corrected for depressive symptoms (aHR: 1.32, CI: 0.97‐1.79, q = 0.292). Conclusions: Type D personality's prevalence amongst IBD patients was comparable with its prevalence in the general population. Type D was strongly associated with depressive symptoms and showed modest independent associations with IBD prognosis. Abstract : The prevalence of Type D personality among IBD patients was comparable to the general population. Type D personality was associated with future episodes of active disease and depressive symptoms. The combination of Type D personality and concomitant depressive symptoms further increased the hazard for future disease recurrence.